New Method for Synthesis of Coatings of Molybdenum, Tungsten, Their Carbides and Composites - Godbole, Rhushikesh V.; More, Mahendra A.; Gupte, Anil S.; Godbole, Vijay P. (Scientific Research, 2013)
In this paper we report, for the first time, a new approach for synthesis of high quality faceted microcrystalline coatings of molybdenum (Mo), tungsten (W), their carbides and composites. These studies are carried out using Hot Filament Chemical Vapor Deposition (HF-CVD) method wherein parent materials (Mo and/or W) are taken in the form of wires (~0.5 mm dia) and are heated to a high temperature (TF ~ 1500 - 2000C), in ambient of “oxygen (O2) diluted hydrogen (H2) gas”. Due to high filament temperature (TF), a series of pyrolytic reactions take place. Firstly, the gasification of wire material (Mo and/or W) occurs in the form of its oxide. The oxide molecules reach the substrate which is kept underneath the filament assembly. Secondly, molecular hydrogen gets dissociated into atomic hydrogen and subsequently reaches the substrate to react with oxide molecules, finally leading to the precipitation of a pure metal. This method can also be used, in situ, to convert metallic coatings into their carbides and/or composites. The method offers many other attractive features, which can not be rendered by the conventional CVD/PVD methods. The results are discussed in terms of temperature induced “Red-ox” reactions.
Keywords: CVD Coatings; Pyrolysis; Ceramics; Refractories